Multiterminal Source Coding Under Logarithmic Loss - Courtade, Thomas A.; Weissman, Tsachy (IEEE transactions on information theory, 2014)
We consider the classical two-encoder multiterminal source coding problem where distortion is measured under logarithmic loss. We provide a single-letter description of the achievable rate distortion region for all discrete memoryless sources with finite alphabets. By doing so, we also give the rate distortion region for the m-encoder CEO problem (also under logarithmic loss). Several applications and examples are given.